“Warriors, Not Victims”: Precious Knowledge, the Fight for Ethnic Studies, and Accountability to the #MeToo Movement - Kannan, Vani; Hernandez, Shyrlene; Martinez, Alexis (Radical Teacher, 2020)
This article shares an upper-division writing course's struggle to be accountable to both the #MeToo movement and the fight for Ethnic Studies in Tucson. These movements collided in our class after we planned a campus screening of the film PRECIOUS KNOWLEDGE, which chronicles the student-led movement to save the Tucson High School Mexican American studies program, and then received news that the director had sexually assaulted one of the student-activists in the film. In this article, collaboratively-written by the professor teaching the course and two students in it, we share our accountability process, and concrete methods for social-movement-accountability in the writing classroom.